Fenomena Cosplay di Kota Medan dalam Perspektif Akidah Islam - Muhammad Riza Fachroni; Mardhiah Abbas; Aprilinda M. Harahap (UIN Sumatera Utara, 2022)
This study aims to determine the phenomenon of cosplay and hijab cosplay in Muslim communities in Medan, cosplay according to contemporary religious experts and scholars, and how to overcome the development of cosplay and hijab cosplay in Medan. The research methodology used is descriptive qualitative method, which is obtained from the results of direct research that goes into the field by expressing words and writing, conducting observations and interviews by conducting question and answer discussions with the subject of cosplay actors in Medan. The findings obtained in this study are that the development of cosplay in Medan City, especially among teenagers, is familiar, where previously, teenagers in Medan City knew about cosplay through various media, both magazines, television, internet, and from various of other social media. At first, cosplay was known among Medan youth through the Bunkasai activity, which was organized by students of the Department of Japanese Literature at the Universitas Sumatera Utara in the implementation of the annual “Japanese Culture Festival” (Bunkasai) in 2008. Cosplay in the lives of teenagers in Medan City has become a habit. And has become a common practice in festival events in the city of Medan, both in Muslim fashion events for female cosplayers and male cosplayers for schools and at the festival level in Medan City which is often carried out at Carefour by using robot costumes or using anime from animated cartoons.